(untitled) (Interdisciplinary Studies Journal, 2026)
This study investigates the practices and knowledge of Creole seed guardians in the Cerrado region of Piauí, particularly in the community of Riacho dos Cavalos, Monte Alegre, PI. The main objective was to understand the social processes underlying these practices, contextualizing them within the structures of habitus and peasant reciprocity, through the life story of one guardian. The methodology employed was qualitative and ethnographic, based on semi-structured interviews and participant observation, with theoretical support from Mauss, Bourdieu, Toledo, and Barrera-Bassols. Content analysis followed Bardin’s precepts. The findings reveal that the circulation of Creole seeds establishes and strengthens social bonds, trust, and cooperation among farmers. This practice constitutes a form of everyday resistance to the homogenization of the agricultural landscape and food insecurity. The guardian studied acts as a mediator of traditional knowledge and a catalyst for solidarity networks, essential for sociocultural reproduction and the safeguarding of biocultural memory. The preservation of these seeds is fundamental to food identity and sovereignty, validating theoretical concepts and offering a practical model for the conservation of agrobiodiversity.